Peningkatan Komunikasi Matematis Siswa Melalui Strategi Discovery Learning Pada Siswa Kelas VII A Semester Gasal SMP Pancasila 13 Paranggupito Tahun 2015/2016 - Nur Widyasmoro, Khalis; , Dra. Sri Sutarni, M.Pd (2015)
The purpose of this study is to describe the increase in students' mathematical communication through Discovery Learning strategies in class VII A junior high school of Pancasila 13 Paranggupito. This research is a classroom action research. A seventh grade students as recipients of actions and mathematics teachers as the giver of action. Data collection methods used were observation, field notes, test and documentation. The data analysis technique used is the process of data analysis, data presentation, and data verification. Results of the study showed an increase in mathematical communication can be seen from: 1) Students are able to ask, answer, and concluded (verbal aspects) (23.8%) increased to (76.19%), 2) Students are capable of using symbol- mathematical symbols correctly (the written aspect) (42.86%) increased to (80.9%), 3) Students are able to transform the problem into an illustration of completion (picture aspect) (33.33%) increased to (71.42% ), and 4) Students are able to explain the mathematical solution (aspect explains the concept) (23.8%) increased to (66.67%). It can be concluded that the application of the Discovery Learning strategies in mathematics can improve mathematical communication.